Unveiling genome plasticity as a mechanism of non-antifungal-induced antifungal resistance in Cryptococcus neoformans - Zheng, Lijun; Xu, Yi; Guo, Liangsheng (Frontiers in Microbiology, 2024)
Cryptococcus neoformans, a critical priority pathogen designated by the World Health Organization, poses significant therapeutic challenges due to the limited availability of treatment options. The emergence of antifungal resistance, coupled with crossresistance, further hampers treatment efficacy. Aneuploidy, known for its ability to induce diverse traits, including antifungal resistance, remains poorly understood in C. neoformans. We investigated the impact of tunicamycin, a well-established ER stress inducer, on aneuploidy formation in C. neoformans. Our findings show that both mild and severe ER stress induced by tunicamycin lead to the formation of aneuploid strains in C. neoformans. These aneuploid strains exhibit diverse karyotypes, with some conferring resistance or cross-resistance to antifungal drugs fluconazole and 5flucytosine. Furthermore, these aneuploid strains display instability, spontaneously losing extra chromosomes in the absence of stress. Transcriptome analysis reveals the simultaneous upregulation of multiple drug resistance-associated genes in aneuploid strains. Our study reveals the genome plasticity of C. neoformans as a major mechanism contributing to non-antifungal-induced antifungal resistance.